Viability in spawn stocks of the white button mushroom, Agaricus bisporus, after freezing in liquid nitrogen without a cryoprotectant - Mata, G; Rodríguez Estrada A.E. (International Journal of Agricultural Technology, 2005)
Three strains of the White Button Mushroom (Agaricus bisporus) were studied. First, spawn was prepared from wheat seeds covered with mycelia, and then placed within polycarbonate vials for freezing in liquid nitrogen. The effect of adding a cryoprotective solution before freezing was evaluated as a function of mycelial growth and percent viability. Two treatments were undertaken: 1) freezing with a glycerol-based cryoprotectant and 2) freezing without a cryoprotectant. Samples were maintained frozen for two weeks, after which time they were thawed and the seeds placed in Petri dishes containing a culture medium. A recovery rate of 96% was obtained for all combined samples in the experiment, whereas 95.8% of the samples frozen without a cryoprotectant were recovered. These results suggest that mycelia can survive frozen storage without cryoprotectants, provided that they are embedded within and protected by the wheat seeds in the spawn. In addition, no significant differences were observed in recovery rates and mycelial diameters between the cryoprotection and non-cryoprotection treatments when a new series of spawn was prepared from the originally-frozen mycelia.